Pengaruh Iklan terhadap Minat Beli Pengguna Youtube dengan Brand Recognition sebagai Variabel Intervening - Yuniyanto, Herdian Rizky; Sirine, Hani (Faculty of Economic and Business, 2018)
The Influence of Advertising on The Buying Interest of Youtube Users with Brand Recognition as Intervening VariableInternet media can be used to do marketing, one of which is Youtube. This study aims to explain the effect of advertising on buying interest on Youtube users using brand recognition as an intervening variable. The sample in this study amounted 180 students of Universitas Kristen Satya Wacana who saw Nike product advertising on Youtube. The analysis technique used is path analysis. The result of the research shows that advertising have a significant positive effect to brand recognition, brand recognition have significant positive effect to buying interest, and brand recognition can not function as intervening variable in relationship between advertising and buying interest.DOI: 10.15408/ess.v8i1.5885